Effect of biofertilizer, vermicompost and chemical fertilizer on different biochemical parameters of Glycine max and Vigna mungo - Javed, Shozeb; Panwar, Aruna (Recent Research in Science and Technology, 2013)
The objective of any agricultural research program is to increase the level of crop productivity. The strategy to boost the level of crop productivity would be through the adoptionof package of practices comprising use of seeds of high yielding varieties, adequate doses of manures and fertilizers and plant protection chemicals. Seed germination is one of the important factors for progressive farming. In present investigation, the effect of plant fertilizers on growth and productivity of Glycine max and Vigna mungo were studied at the various concentrations of fertilizers. We used Biofertilizer (B), Vermicompost (V), Chemical fertilizer (C) and combination of these three. It was found that,the seed germination percentage was high in Vermicompost treated soil in Vigna mungo and Biofertilizer treated in Glycine max. Vigna mungo protein content was found high in B+C treated soil, while carbohydrate and phenol content increased in B+V treated soil. High seed germination was observed in vermicompost treated soil .In case of Glycine max, carbohydrate content increased in C+V+B treated soil ,protein and phenol content observed max. in vermicompost treated soil and high seed germination % observed in biofertilizer treated soil.